An unexpected complication of intracardiac device implantation: Contralateral pneumothorax and pneumopericardium - Parashar, Nitin Kumar (Indian Pacing Electrophysiol J, 2019)
A 62-year-old man developed concomitant right-sided pneumothorax and pneumopericardium after undergoing implantation of a left-sided dual-chamber pacemaker. The case is reported for its rarity. The possible mechanisms and management options for this extremely rare complication are discussed.